Agriculture in Nicaragua : promoting competitiveness and stimulating broad-based growth. (World Bank country study., 2003)
"Broad-based growth is one of the four pillars of the Nicaraguan Government's Poverty Reduction Strategy. Living standards of the rural poor will continue to depend largely upon agriculture. This study takes stock of major developments in Nicaragua's agricultural sector and argues that broad-based growth can be promoted by strengthening agricultural competitiveness. Export growth is the key, requiring immediate action within a coherent strategy. The case of coffee illustrates the proposed strategy. This report also identifies productivity constraints in rural factor markets, suggesting medium- and long-term solutions. It concludes with a review of the issue of risk management and with descriptions of some promising pilot projects."--Jacket